Analisis Informasi Kandungan Produk Pinkflash Di Media Sosial Terhadap Kepercayaan Konsumen - Dwi Sulistiyawati; Zakiyatul Amalia Saputri; Azri Amalan Tsalis; Rio Kurniawan (Universitas Pakuan, 2026)
ANALYSIS OF PINKFLASH PRODUCT CONTENT ON SOCIAL MEDIA IN RELATION TO CONSUMER TRUST Social media has become one of the primary sources of information that people use when seeking references regarding beauty products, including information about a product’s ingredients and safety. This study aims to analyze the impact of information dissemination regarding Pinkflash product ingredients on social media on consumer trust levels and to examine the communication strategies employed by the company in addressing this issue. This study employs a qualitative approach using a phenomenological method through observation, interviews, and documentation. The results indicate that information circulating on social media regarding Pinkflash product ingredients influences consumers’ perceptions of product safety and quality. Some consumers experienced a decline in trust following exposure to negative information, while others maintained their trust based on their product usage experience and the credibility of the information sources they relied on. Furthermore, transparent and responsive communication strategies have proven to play a crucial role in maintaining and restoring consumer trust in Pinkflash products. This study concludes that the dissemination of information on social media has a significant influence on the formation of consumer trust; therefore, companies need to implement effective communication strategies to maintain their public image and trust.